Organ dose calculator for diagnostic nuclear medicine patients based on the ICRP reference voxel phantoms and biokinetic models. (1st January 2023) - Villoing, Daphnée; Kwon, Tae-Eun; Pasqual, Elisa; Kitahara, Cari M; Lee, Choonsik
Abstract: The exponential growth in the use of nuclear medicine procedures represents a general radiation safety concern and stresses the need to monitor exposure levels and radiation-related long term health effects in NM patients. In the current study, following our previous work on NCINM version 1 based on the UF/NCI hybrid phantom series, we calculated a comprehensive library of S values using the ICRP reference pediatric and adult voxel phantoms and established a library of biokinetic data from multiple ICRP Publications, which were then implemented into NCINM version 2. We calculated S values in two steps: calculation of specific absorbed fraction (SAF) using a Monte Carlo radiation transport code combined with the twelve ICRP pediatric and adult voxel phantoms for a number of combinations of source and target region pairs; derivation of S values from the SAFs using the ICRP nuclear decay data. We also adjusted the biokinetic data of 105 radiopharmaceuticals from multiple ICRP publications to match the anatomical description of the ICRP voxel phantoms. Finally, we integrated the ICRP phantom-based S values and adjusted biokinetic data into NCINM version 2. The ratios of cross-fire SAFs from NCINM 2 to NCINM 1 for the adult phantoms varied widely from 0.26 to 5.94 (mean = 1.24, IQR = 0.77–1.55) whereas the ratios for the pediatric phantoms ranged from 0.64 to 1.47 (mean = 1.01, IQR = 0.98–1.03). The ratios of absorbed dose coefficients from NCINM 2 over those from ICRP publications widely varied from 0.43 (colon for 99m Tc-ECD) to 2.57 (active marrow for 99m Tc-MAG3). NCINM 2.0 should be useful for dosimetrists and medical physicists to more accurately estimate organ doses for various nuclear medicine procedures.